Analisis hubungan angin zonal dan angin meridional lapisan 850 milibar terhadap curah hujan di Sumatera Barat - Lili Sartika (PILLAR OF PHYSICS, 2016)
This study was conducted to determine the effect of zonal wind and meridional wind layer 850 millibars to rainfall in Sumatra Barat. Additionally, it also obtained the pattern of both zonal wind and meridional wind that give impact to rainfall in West Sumatra. This study used rainfall data that were taken monthly, wind zonal and meridional winds of 850 millibars layer equivalent to 1.4 km from 1998 to 2015. Defining relationships zonal wind and meridional wind on the distribution of posts precipitation of rain in three regions, ie the waterfront area, mountainous regions and areas behind the mountains. The division of this region to give a picture of wind patterns that affect rainfall in West Sumatra. Influence of zonal wind and meridional wind to precipitation was analyzed using canonical correlation analysis using software Climate Predictability Tool (CPT). while to see the patterns of wind zonal and meridional wind using software The Grid Analysis and Display System (Grads) version 2.0. The result showed zonal wind relation to rainfall resulted in moderate correlation in March with a correlation coefficient (r = 0.45) whereas the meridional wind has a low correlation (r = 0.37). In November of zonal wind has a low correlation with a correlation coefficient (r = 0.36) compared to the meridional winds that showed a strong correlation (r = 0.60). So rainfall that occurred in West Sumatra is predominantly influenced by the zonal wind in March, while in November more influenced meridional wind. Meanwhile, wind patterns that affect rainfall in West Sumatra have equatorial wind pattern and the pattern of the monsoon